Optimal pacing strategy: from theoretical modelling to reality in 1500-m speed skating - Hettinga, F. J.; de Koning, J. J.; Schmidt, L. J. I.; Wind, N. A. C.; MacIntosh, B. R.; Foster, C. (British Journal of Sports Medicine, 2011)
Purpose Athletes are trained to choose the pace which is perceived to be correct during a specific effort, such as the 1500-m speed skating competition. The purpose of the present study was to "override" self-paced (SP) performance by instructing athletes to execute a theoretically optimal pacing profile.